Age of information-oriented sampling and power control in vehicular status update networks - Jianhua ZENG; Chongtao GUO; Cheng GUO (物联网学报)
In a vehicular status update network based on broadcast communication, a D/Geo/1/1 queuing mechanism with minimum timestamp priority was adopted to transmit data packets.The queuing theory was used to analyze the age-ofinformation (AoI) outage probability of the receivers and the average transmit power of the transmitter.Based on the monotonicity of the AoI outage probability with respect to packet sampling rate and transmit power, an iterative algorithm for jointly optimizing sampling rate and transmit power was proposed to minimize the maximum AoI outage probability of all receivers under power constraint, which fairly improved information freshness of all receivers under sampling and power control.Simulation results verify the accuracy of theoretical analysis and the efficiency of the algorithm.